(untitled) - Palmer, Tim (Washington, D.C., 1996)
The book represents the culmination of that grand adventure. Palmer describes the rivers of America in all their remaining glory and tarnished beauty, as he presents a comprehensive tour of the whole of America's river systems
Keywords: Rivers; United States